Implementasi Laporan Berkelanjutan Pada Pemerintahan Daerah Kabupaten Sleman - Mamluatul Marzuqoh; Zulfatun Ruscitasari (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This research analyzes the implementation of sustainability reporting in the Sleman Regency Government with a focus on applying Global Reporting Initiative (GRI) standards in economic (GRI 200) and environmental (GRI 300. Through a descriptive qualitative approach, this study collected primary data from interviews with relevant officials and secondary data from policy documents such as the Regional Medium-Term Development Plan and regional financial reports. The results show that Sleman Regency has implemented sustainable economic aspects through stable economic growth, transparent procurement practices, and anti-corruption programs. In environmental aspects, there has been significant progress in waste management reaching 52.91% and proper access to domestic wastewater at 84.52%, although still facing challenges in optimizing environmental management facilities. The research concludes that the implementation of GRI-based sustainability reporting has the potential to improve transparency, accountability, and effectiveness of governance, as well as support the achievement of Sustainable Development Goals (SDGs). It is recommended to enhance socialization of sustainable environmental management, optimize waste and wastewater management facilities, and strengthen evaluation mechanisms for sustainability programs.